The Wythenshawe Hybrid Circuit for lung transplantation: a previously undescribed circuit for lung transplant. (April 2020) - Brazier, Andrew; Seville, Edward; Hesford, Wesley; Pate, Bryce; Exton, Paul; Sinstadt, Naomi; Sanders, Megan; Dosouto, Elena; Barnard, James B
Extracorporeal membrane oxygenation is a safe modality of cardiorespiratory support for lung transplantation, with a reduction in coagulopathy and transfusion requirement when compared with cardiopulmonary bypass. In some scenarios, in lung transplantation, there are advantages to the use of cardiopulmonary bypass, which allows cardiac decompression, filtering of embolic air, easy addition and removal of volume, and a means to immediately reintroduce lost blood into circulation. We describe a novel circuit which allows safe and easy switch between modalities without prolonged interruption of flow. This circuit offers a safety net during surgery to minimise the risks influencing the use of extracorporeal membrane oxygenation.